Behavior of Bi2S3 under ultrasound irradiation for Rhodamine B dye degradation - Teodoro, Vinícius; Barrios Trench, Aline; Guerreiro da Trindade, Letícia [UNESP]; Jacomaci, Natalia [UNESP]; Beltran-Mir, Hector; Andrés, Juan; Cordoncillo, Eloisa; Bettini, Jefferson; Longo, Elson (Elsevier, 2021)
In this study, we have demonstrated that Bi2S3 semiconductor under ultrasound behaves as a piezoelectric material, facilitating the transfer of electrons and holes, thus enabling the formation of oxidizing agents. In the presence of light, Bi2S3 showed no photocatalytic activity, resulting in Rhodamine B (RhB) degradation of 2.5%, while the ultrasound application led to a degradation of 40.6%. Herein, we propose a possible mechanism to explain this behavior based on the local charge polarization in [BiS7] clusters.
Keywords: Bismuth sulfide; Photocatalysis; Piezocatalysis; Ultrasound